Understanding the role of alkaline phosphatase as a possible marker for the evaluation of antiparasitic agents - Gustavo A. Martínez, Luis E. Trujillo (Journal of Applied Pharmaceutical Science, 2018)
The release of alkaline phosphatase (AP) into media provides an enzymatic method for the evaluation of the effectiveness of antiparasitic drugs in vitro. However, to date, it has only been applied sporadically in some cestodes and trematodes. In this paper, we describe for the first time a cost-effective evaluation method to accurately determine larvae immobility or mortality after salt or starvation stress treatment in order to measure the released parasitic AP as an enzymatic stress marker. Our method avoids tedious and time-consuming visual counting of the model organism, human parasite nematode Strongyloides venezuelensis larvae. In opposition to previous reports, we found a linear relationship between larval immobilization due to stress treatment and the released AP from L3 larvae. This method could be applied to a preclinical evaluation of active antiparasitic compounds in AP producing nematodes and other parasites.
Keywords: Alkaline phosphatase, larval mortality, Strongyloides venezuelensis, parasites, larvae immobility.